TEACHERS' BELIEFS ABOUT EFL LEARNING STRATEGIES AND CLASSROOM PRACTICES - Wijirahayu, Suciana (2015)
The purpose of this multiple case study was to examine whether teachers' beliefs about EFL Learning Strategies were reflected in their actual classroom practices. There were seven teachers who participated in this research. One of the data gathering instruments in this case study was a questionnaire that inquires the participants beliefs about EFL Learning Strategies (BALLI and SILL) to the classroom practices and how these beliefs influence their classroom practices in Primary, Junior High as well as Senior High education. In addition to the questionnaire, semi structured interviews with participants were held to examine their beliefs in detail. Finally, in order to see whether participants' beliefs matched with their actual practices in their classrooms practices, the participants were observed and video-recorded for triangulation for the data. Three sessions classroom observations of the courses as well as video recordings of those courses were also examined by the researcher. O'Malleys language learning strategies scheme was used to classify the transcript of classroom video recordings. The result of the analysis of participants' responses to the questionnaire, video-recorded classroom observations and interviews were presented qualitatively in the findings section. The results showed that all of the seven teachers beliefs about EFL Learning strategies were uniquely reflected in their classroom practices suitable to their experience in acquiring and applying LLS in learning English. Moreover, the finding shows that teachers beliefs were interrelated and strengthened by the experience of applying LLS in their classroom practices. Key words: Teacher's beliefs about language learning, Language Learning Strategies, multiple case study.